Model Penunjang Keputusan Jadwal Produksi Jus Buah Segar - Maflahah, Iffan; Machfud, Machfud; Udin, Faqih (Department Industrial Engineering, University of Muhammadiyah Malang, 2012)
Planning and production control are important factors to determine the efficiency derived through proper managementÂ of raw material supply of fresh fruits, production planning and master production schedule. This research aimed to developÂ the aggregate production planning model, and master production schedule model for juice production from fresh fruit, while also considered the perishability of the fresh fruit. There were several methods applied in the works, namely autoregressive integrated moving average (ARIMA) for forecasting of raw material product sale, mathematical model for raw material supply, linear programming for production planning and prospective production scheduling to develop master production schedule. This research developed software for decision support system called RP_JUS. The results showed that all raw material damage was distributed exponentially. Decision Support Model of Production Schedule for Fresh Fruit Juice can be applied to the processing indudtries that use fresh fruit.